A Cascaded Reduced-Dimension STAP Method for Airborne MIMO Radar in the Presence of Jammers - Wang, Ting; Zhao, Yongjun; Chen, Shiwen; Zhang, Kunfan (Společnost pro radioelektronické inženýrství, 2017)
A cascaded reduced-dimension (RD) space-time adaptive processing (STAP) method for airborne multiple-input multiple-output (MIMO) radar in the presence of jammers is proposed in this paper. The proposed MIMO-STAP method for clutter plus jamming suppression proceeds in two steps. Firstly, the jamming is suppressed by its orthogonal complementary subspace obtained in the passive radar mode, while the receive dimension is reduced. Secondly, the tri-iterative algorithm (TRIA) is utilized to suppress the clutter combining the remaining receive degree of freedom (DOF) with the transmit DOF and the Doppler DOF, and further dimension reduction is implemented. The proposed method can effectively realize the separate jamming and clutter elimination. Moreover, the training sample number and the computational complexity are significantly decreased. Simulation results verify the validity of the proposed cascaded RD MIMO-STAP method under jamming condition.
Keywords: Multiple-input multiple-output (MIMO) radar; space-time adaptive processing (STAP); dimension reduction; jammer; tri-iterative algorithm (TRIA)